2021
DOI: 10.3389/feart.2020.587085
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of Non-Steady State Transport Dynamics on the Sulfur and Oxygen Isotope Composition of Sulfate in Sedimentary Pore Fluids

Abstract: We present the results of an isotope-enabled reactive transport model of a sediment column undergoing active microbial sulfate reduction to explore the response of the sulfur and oxygen isotopic composition of sulfate under perturbations to steady state. In particular, we test how perturbations to steady state influence the cross plot of δ34S and δ18O for sulfate. The slope of the apparent linear phase (SALP) in the cross plot of δ34S and δ18O for sulfate has been used to infer the mechanism, or metabolic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 101 publications
1
10
0
Order By: Relevance
“…It appears that the oxygen isotopic composition of sulfate may increase slightly faster than the sulfur isotopic composition of sulfate at Site 11 (Figure 4A). At one of the sites with piston core data (Site 9; 2,323 mbsl) we note that the cross plot of δ 34 S SO4 vs. δ 18 O SO4 (Figure 4A) comes out of the apparent linear phase, where the sulfur and oxygen isotopic compositions covary, and into the equilibration phase, where δ 18 O SO4 has reset through oxygen isotope equilibrium with water intracellularly and does not change further as the δ 34 S SO4 values continue to increase (Antler et al, 2014;Antler and Pellerin, 2018;Fotherby et al, 2021). The carbon isotope composition of the DIC decreases with depth as expected from the oxidation of organic carbon and the return of 12 C-rich carbon to the DIC pool (Figures 2G,H).…”
Section: Resultsmentioning
confidence: 87%
“…It appears that the oxygen isotopic composition of sulfate may increase slightly faster than the sulfur isotopic composition of sulfate at Site 11 (Figure 4A). At one of the sites with piston core data (Site 9; 2,323 mbsl) we note that the cross plot of δ 34 S SO4 vs. δ 18 O SO4 (Figure 4A) comes out of the apparent linear phase, where the sulfur and oxygen isotopic compositions covary, and into the equilibration phase, where δ 18 O SO4 has reset through oxygen isotope equilibrium with water intracellularly and does not change further as the δ 34 S SO4 values continue to increase (Antler et al, 2014;Antler and Pellerin, 2018;Fotherby et al, 2021). The carbon isotope composition of the DIC decreases with depth as expected from the oxidation of organic carbon and the return of 12 C-rich carbon to the DIC pool (Figures 2G,H).…”
Section: Resultsmentioning
confidence: 87%
“…3). Compared to the range of  34 S SO4 and  18 O values in modern sediment pore waters where microbial sulfate reduction is active (blue area in figure 3) (Fotherby et al, 2021), the range of  34 S SO4 corresponding to Primary Lower Gypsum and Upper Gypsum deposits is limited (Fig. 3).…”
Section: Analytical Resultsmentioning
confidence: 89%
“…Other processes are known to have an effect on the δ18OitalicSO4 vs. δ34SitalicSO4 plot such as the sulfide and pyrite oxidation (Balci et al, 2007) and disproportionation (Böttcher et al, 2001, 2005); however, their effect should only decrease the relative estimated calculated rates of MSR. Additionally, it was shown that when the sulfate reduction rates are high (i.e., the δ18OitalicSO4 vs. δ34SitalicSO4 slope is low), the effect of transport such as diffusion and sedimentation is negligible on the measured slope (Fotherby et al, 2020). Such a plot can be adapted to the form of (δ18OitalicSO4δ18OSO4,0) vs. (δ34SitalicSO4δ34SSO4,0), where δ18OSO4,0 and δ34SSO4,0 are the initial SO 4 2− isotope values, thereby negating the “source effect” and allowing data with a linear relationship from various aquatic and subsurface environments beyond the Dead Sea to be compared (e.g., lakes, seas, estuaries, and salt marshes) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Other processes are known to have an effect on the δ 18 O SO 4 vs. δ 34 S SO 4 plot such as the sulfide and pyrite oxidation (Balci et al, 2007) and disproportionation (Böttcher et al, 2001(Böttcher et al, , 2005; however, their effect should only decrease the relative estimated calculated rates of MSR. Additionally, it was shown that when the sulfate reduction rates are high (i.e., the δ 18 O SO 4 vs. δ 34 S SO 4 slope is low), the effect of transport such as diffusion and sedimentation is negligible on the measured slope (Fotherby et al, 2020). Such a plot can be adapted to the form of (δ Stable δ 34 S SO 4 and δ 18 O SO 4 from primary gypsum layers found in the Dead Sea sedimentary record were also used to investigate rates of MSR using a similar isotope plot given that the effect of isotope fractionation during gypsum precipitation has a negligible effect on the slope (Torfstein & Turchyn, 2017).…”
Section: Sulfatementioning
confidence: 99%